A Note on Selling Costs and the Equilibrium of the Firm - Hayes, J. P. (Review of Economic Studies, 1944)
Journal Article A Note on Selling Costs and the Equilibrium of the Firm Get access J. P. Hayes J. P. Hayes Oxford Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 12, Issue 2, 1944, Pages 106–109, https://doi.org/10.2307/2296094 Published: 01 September 1944